Allatostatin-type A, kisspeptin and galanin GPCRs and putative ligands as candidate regulatory factors of mantle function - Cardoso, João CR (2017)
Allatostatin-type A (AST-A), kisspeptin (KISS) and galanin (GAL) G-protein coupled receptor (GPCR) systems share a common ancestral origin in arthropods and the vertebrates where they regulate metabolism and reproduction. The molluscs are the second most diverse phylum in the animal kingdom, they occupy an important phylogenetic position, and their genome is more similar to deuterostomes than the arthropods and nematodes and thus they are good models for studies of gene family evolution and function. This mini-review intends to extend the current knowledge about AST-A, KISS and GAL GPCR system evolution and their putative function in the mollusc mantle. Comparative evolutionary analysis of the target GPCR systems was established by identifying homologues in genomes and tissue transcriptome datasets available for molluscs and comparing them to those of other metazoan systems. Studies in arthropods have revealed the existence of the AST-A system but the loss of homologues of the KISS and GAL systems. Homologues of the insect AST-AR and vertebrate KISSR genes were found in molluscs but putative GALR genes were absent. Receptor gene number suggested that members of this family have suffered lineage specific evolution during the molluscan radiation. In molluscs, orthologues of the insect AST-A peptides were not identified but buccalin peptides that are structurally related were identified and are putative receptor agonists. The identification of AST-AR and KISSR genes in molluscs strengthens the hypotheses that in metazoans members of the AST-AR subfamily share evolutionary proximity with KISSRs. The variable number of receptors and large repertoire of buccalin peptides may be indicative of the functional diversity of the AST-AR/IGSSR systems in molluscs. The identification of AST-A and KISS receptors and ligands in the mantle transcriptome indicates that in molluscs they may have acquired a novel function and may play a role in shell development or sensory detection in the mantle.